PENGARUH GRADED REPETITIVE ARM SUPPLEMENTARY PROGRAM (GRASP) TERHADAP KEMAMPUAN KONTROL MOTORIK EKSTREMITAS ATAS DAN KEMANDIRIAN FUNGSIONAL PASIEN PASCA STROKE - Kurniawan, Hendri; Rita Untari (Medical Journal of Nusantara, 2024)
Stroke causes sensorimotor dysfunction that affects motor control ability and functional independence. Post-stroke recovery is influenced by repetitive sensorimotor stimulation. Recovery of motor control ability and functional independence of post-stroke patients often do not provide optimal results. This is thought to be related to the continuity of exercise performed by the patient. The Graded Repetitive Arm Supplementary Program (GRASP) is an exercise program designed to be carried out independently by post-stroke patients at home. This study aims to determine the effect of GRASP on upper extremity motor control ability and functional independence of post-stroke patients.                Quantitative research using a quasi-experimental design with a control group pretest-posttest design. A sample of 50 people was obtained using a purposive sampling technique. The motor control was measured using the Fugl-Meyer Assessment Upper Extremity but functional independence was measured using Barthel index instruments. Data analysis used the t-test with SPSS 25 software.  The majority of the samples were male (86%) and experienced upper extremity motor control disorders with an average score of 40.32 (treatment) and 40.88 (control). The functional independence of the sample was in the moderate dependence category with an average score of 75.26 (treatment) and 76.04 (control). After the intervention, the average motor ability score became 43.37 (treatment) and 42.53 (control) which was accompanied by a change in the average functional independence score to 81.25 (treatment) and 79.43 (control) although it was still in the moderate dependence category. The paired t-test on motor ability and functional independence showed significance of 0.000 and 0.001 (treatment group) and 0.004 and 0.001 (control group). The unpaired t-test showed a significance of 0.002 (motor ability) and 0.015 (functional independen) GRASP is more significant in influencing the improvement of upper extremity motor control ability and functional independence of post-stroke patients.